Novel strategies for assessing the pitting corrosion resistance of stainless steel surfaces. Issue 8 (2nd October 2012) - Burkert, A.; Klapper, H. S.; Lehmann, J.
Abstract Pitting corrosion is one of the most common mechanisms of surface damage on stainless steels. Electrochemical methods have been preferentially applied for the evaluation of the pitting corrosion resistance of stainless steels in the laboratory. Nevertheless, some of them are not reliable enough and in general the application of electrochemical methods in the field becomes difficult because of required deep understanding of corrosive phenomena and measurement technology. Therefore, new approaches for the evaluation of the pitting corrosion susceptibility of stainless steel surfaces in the laboratory as well as in the field are necessary. In the present paper two novel strategies including electrochemical noise measurements under anodic polarization for laboratory testing, and an indicator test to assess the susceptibility of stainless steel surfaces to pitting corrosion in the field are introduced. Experimental results concerning the influence of surface treatments on the pitting corrosion resistance on stainless steels have confirmed that final surface condition has a significant effect on their future pitting corrosion susceptibility. In addition, the pitting corrosion resistance of stainless steel surfaces was observed being specifically dependent on the achieved surface topography and in some cases independent on the roughness parameters of the surface.